PENGARUH PERMODALAN RENTABILITAS DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA BANK PANIN DUBAI SYARIAH PERIODE 2018-2020 - Rusman Azizoma; Urwatun Usko (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2023)
This study aimed to determine the effect of Capital Adequacy Ratio (CAR), Operating Expense to Operating Income (BOPO), and Financing to Deposit Ratio (FDR) on Return on Assets at Sharia Panin Dubai Bank from 2018-2020. This is quantitative research gathered data from secondary data where the population was the financial report uploaded on the official website of the bank. The analytical technique used is an associative analysis using the Partial Least Square 3.0 (PLS) application. The findings showed that the Capital Adequacy Ratio partially negatively and insignificantly affected the Return on Assets, Financing to Deposit Ratio partially positively and insignificantly affected the Return on Assets, and Operating Expense to Operating Income partially positively and significantly affected the Return on Assets.Keywords: Capital Adequacy Ratio (CAR); Operating Expense to Operating Income (BOPO); Financing to Deposit Ratio (FDR);  Return on Assets (RoA)